Removal of Basic Blue-9 Dye from Water by Eugenia jambolana Seeds and Citrullus lanatus Peels - Rehman, Rabia; Luqman, Wajeeha (Asian Journal of Chemistry, 2014)
Sorption of basic blue 9 dye from aqueous solution on the surface of Eugenia jambolana seeds (Jamun seeds or J.S) and Citrullus lanatus peels (Watermelon peels or W.M.P) was accomplished under the optimize conditions of temperature, pH, contact time, agitation speed and adsorbent dose. Both adsorbents were characterized for seeking different functional groups and unsaturation that can act as possible active sites for biosorption. The values of qmax data for basic blue-9 dye sorption on W.M.P (35.714 mg g-1) showed better removing capacity as compared to J.S. (4.902 mg g-1). Thermodynamic parameter 'DGo' indicated that basic blue-9 sorption on jamun seeds and watermelon peels exhibit spontaneous and exothermic behaviour. The results of these investigations suggested that these agro-wastes can be utilized as sorbent materials for basic blue-9 dye removal from waste-water streams.